2000
DOI: 10.1002/(sici)1521-3757(20000515)112:10<1878::aid-ange1878>3.0.co;2-4
|View full text |Cite
|
Sign up to set email alerts
|

Metamorphic Channels in Periodic Mesoporous Methylenesilica

Abstract: Verbrückende Methylengruppen werden in terminale Methylgruppen überführt, wenn periodisch mesoporöse Methylensilicate, die erstmals durch Tensid‐Templat‐Synthese hergestellt wurden, unter kontrollierten Bedingungen (350–600°C) getempert werden. Die Methylengruppen, die zunächst Bestandteil der Kanalwände sind, werden dabei zu Methylgruppen, die in die Kanäle hineinragen (siehe Schema).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…Periodic mesostructured organosilicas (PMOs) [138] are a relatively new class of functional mesoporous material receiving a great deal of attention in recent years [139], and the Ozin group has been one of the leaders in this field [140]. In some ways, the PMO concept is a logical extension of the co-condensation process, the key difference being that the PMO materials are built around functional organo di-or tri-silanes.…”
Section: Periodic Mesostructured Organosilicasmentioning
confidence: 99%
“…Periodic mesostructured organosilicas (PMOs) [138] are a relatively new class of functional mesoporous material receiving a great deal of attention in recent years [139], and the Ozin group has been one of the leaders in this field [140]. In some ways, the PMO concept is a logical extension of the co-condensation process, the key difference being that the PMO materials are built around functional organo di-or tri-silanes.…”
Section: Periodic Mesostructured Organosilicasmentioning
confidence: 99%
“…[11][12][13] These bridging organic groups impart unique chemical, biological, optical, and dielectric properties to PMO and distinguish PMO from its pure siliceous counterpart. 14,15 We use methane PMO, with a -CH 2 -bridge, as an archetype to demonstrate our patterning technique because at a temperature higher than 400 °C, the transformation of bridging -CH 2 -groups into terminal -CH 3 groups hydrophobizes the surface of the pore wall 10,16,17 and exposes the terminal methyl groups for subsequent plasma treatment. Another PMO that can be similarly hydrophobized is 3-ring PMO; in contrast, ethane and ethene PMO do not possess this ability.…”
Section: Resultsmentioning
confidence: 74%
“…The first report of methylene-bridged PMOs was by Asefa et al in 2000. [54] Longer chain alkylene PMOs, such as alkylene spacers containing urea functionalities or hexylene spacers, were not reported until the mid-2000s to early 2010s. [55][56][57][58] Researchers found that it is often difficult to synthesize highly ordered PMOs containing long alkylene moieties due to solubility limitations.…”
Section: Synthesis Of Chiral Nematic Mesoporous Organosilica With Alkmentioning
confidence: 99%